ENTERPRISE-SCALE CLOUD MIGRATION: A STRATEGIC DIGITAL EVOLUTION - Srinivas Reddy Pinnapureddy (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This technical article examines Nestlé's comprehensive cloud transformation journey, highlighting the company's strategic partnership with SAP and its evolution from traditional infrastructure to a modern cloud-based enterprise architecture. It explores the technical challenges, implementation strategies, and benefits realized through this large-scale digital transformation initiative. The article details the architectural considerations, data integration approaches, and security frameworks implemented across the organization's global operations. It examines how Nestlé successfully modernized its infrastructure while maintaining business continuity, implementing advanced analytics capabilities, and enhancing customer engagement platforms. The article also discusses the future technical roadmap, including the evolution towards more sophisticated cloud implementations incorporating artificial intelligence, machine learning, and advanced analytics capabilities. Through this transformation, Nestlé has demonstrated how large enterprises can successfully navigate complex digital transformations while maintaining operational efficiency and creating a foundation for future innovation.